2000
DOI: 10.1083/jcb.151.3.697
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Activity of Myosin Light Chain Kinase Isoforms during the Cell Cycle

Abstract: Phosphorylation on Ser 19 of the myosin II regulatory light chain by myosin light chain kinase (MLCK) regulates actomyosin contractility in smooth muscle and vertebrate nonmuscle cells. The smooth/nonmuscle MLCK gene locus produces two kinases, a high molecular weight isoform (long MLCK) and a low molecular weight isoform (short MLCK), that are differentially expressed in smooth and nonmuscle tissues. To study the relative localization of the MLCK isoforms in cultured nonmuscle cells and to determine the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 63 publications
(95 reference statements)
12
97
4
Order By: Relevance
“…Also, within a single cell, GFP-DAPk was not evenly distributed on the filaments, with some areas of individual stress fibers containing more DAPk than others (compare shades of yellow and orange of overlap in right panel of Figure 1b), and some fibers lacking visible GFP-DAPk. This contrasts with the previously described long myosin light chain kinase (MLCK L -GFP) fusion, 24 which localizes to well-organized, thick filaments (e.g. Figure 1a) that coincide completely and uniformly with actin stress fibers (Figure 1c), extending to the focal contacts (Figure 1e).…”
Section: Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…Also, within a single cell, GFP-DAPk was not evenly distributed on the filaments, with some areas of individual stress fibers containing more DAPk than others (compare shades of yellow and orange of overlap in right panel of Figure 1b), and some fibers lacking visible GFP-DAPk. This contrasts with the previously described long myosin light chain kinase (MLCK L -GFP) fusion, 24 which localizes to well-organized, thick filaments (e.g. Figure 1a) that coincide completely and uniformly with actin stress fibers (Figure 1c), extending to the focal contacts (Figure 1e).…”
Section: Resultscontrasting
confidence: 92%
“…Figure 1a) that coincide completely and uniformly with actin stress fibers (Figure 1c), extending to the focal contacts (Figure 1e). In fact, expression of MLCK results in increased fiber formation in these same cells (see also Poperechnaya et al 24 and Blue et al 25 ). GFP alone, in contrast, exhibited a diffuse cytoplasmic localization with strong nuclear accumulation (Figure 1a), and showed no significant overlap with actin filaments (data not shown).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…It is hypothesized that binding to F-actin via DFRXXL and to myosin via telokin facilitates RLC phosphorylation by MLCK. When the 5DFRXXL region was deleted, the full length or N-terminus of long MLCK could still bind to stress fiber, implying the existence of a novel binding motif in the extension region [23][24][25]. Furthermore, Poperechnaya et al found that, in dividing cells, the extension region was required for MLCK localization to the cleavage furrow.…”
Section: F-actin Binding Of Long Mlck 368mentioning
confidence: 99%